(untitled) (Research, Society and Development, 2024)
Contemporary communication has been significantly transformed by electronic devices, pushing boundaries and connecting people globally. Technologies such as telehealth and social media have become vital, especially during the COVID-19 pandemic, promoting health and facilitating remote interaction and care. However, increased technosociality has brought challenges such as the “infodemic” and misinformation, highlighting the crucial role of healthcare professionals in education and dissemination of truthful information. The present study aimed to highlight the use of Information and Communication Technology (ICT) in health promotion by professionals in primary care. This is an integrative review of the literature, in which studies published in the period between 2020 and 2024 were selected and included, through the databases of the Virtual Health Library, Latin American and Caribbean Literature in Health Sciences and Scientific Electronic Library Online. After applying the inclusion and exclusion criteria, 12 studies were selected to compose this review. The use of ICT provides opportunities to promote health, facilitating the development of health actions, overcoming geographic limitations and offering safe reception and monitoring for patients. In this way, it is possible to observe the ease of promoting health in primary health care, reducing the waiting list and welcoming patients online, but it also presents risks due to the dissemination of fake news.